PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PENERAPAN STRATEGI DIFERENSIASI UNTUK MENCIPTAKAN KEUNGGULAN BERSAING - Sari, Rika Catur Arum (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out how far is the Corporate Social Responsibility has been conducted and the implementation of differentiate strategy as an instrument to create the competitive advantage at PT. Mandiri Tunas Finance. The method of this research is using qualitative method, because researcher are not yet analyzed the hypothesis test on Corporate Social Responsibility and Differentiation Strategies adopted by the PT. Mandiri Tunas Finance. The research result found that the Corporate Social Responsibility activity the purpose of the external is for the society empowerment, such as social, healty, environment, and scholarship program for students. And the purpose of the internal activity is to the employeesâ prosperity, such as giving recruitment and training. The differentiation strategy does is launched the new program which is ACP (Insurance Credit Protection). The analysis result shows that the Corporate Social Resposibility activity for the internal has increased by 42.28% and for the external activity has increased by 84%. The companyâs financial performance is also increasing since the company has implemented the Corporate Social Responsibility and Differentiation Strategy. The conclusion of this research shows that CSR and Differentiation strategy which has been implemented is giving many advantages for the company as well as increasing the financial performance at PT. Mandiri Tunas Finance, therefore, it is giving a positive impact for the company to increase competitive advantage. Keywords: Corporate Social Responsibility, Differentiation Strategy, and Competitive Advantage.